1987
DOI: 10.1128/mcb.7.3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Multiple proteins bind to VA RNA genes of adenovirus type 2.

Abstract: Using fractionated HeLa cell nuclear extracts and both nuclease (DNase I) cleavage and chemical cleavage (methidiumpropyl-EDTA-Fe(II) protection methodologies, we demonstrated the presence of three proteins which interacted specifically, yet differentially, with the two VA genes of adenovirus type 2. One, previously identified as transcription initiation factor TFIIIC, bound to a site centered on the transcriptionally essential B-block concensus element of the VAI gene and, with a lower affinity, to the analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
(47 reference statements)
1
21
1
Order By: Relevance
“…On the basis of further experiments carried out in vitro, it was suggested that NF1 can function as a general pol III transcription factor, influencing expression of a range of class III genes (31). The study, however, ignored an earlier paper from the same laboratory that had concluded that NF1 has no effect on VA gene transcription (45). We used ChIP assay to test whether NF1 is present at class III genes in vivo.…”
Section: Nf1 and Tfiia Are Not Detected At Pol Iii-transcribed Genes mentioning
confidence: 97%
“…On the basis of further experiments carried out in vitro, it was suggested that NF1 can function as a general pol III transcription factor, influencing expression of a range of class III genes (31). The study, however, ignored an earlier paper from the same laboratory that had concluded that NF1 has no effect on VA gene transcription (45). We used ChIP assay to test whether NF1 is present at class III genes in vivo.…”
Section: Nf1 and Tfiia Are Not Detected At Pol Iii-transcribed Genes mentioning
confidence: 97%
“…1). The deoxyribonuclease I (DNase I) footprinting pattern observed for the USF-TFIID-ML promoter complex (lane 3) analyzed by DNase I footprinting as described (10,16). The products of adenosine-(A) and guanosine-specific (G) chemical-sequencing reactions (24) were used as markers.…”
Section: G Ene Activity In Eukaryotes Ismentioning
confidence: 99%
“…DNase I cleavage was initiated by the addition of 3 ng of DNase I and allowed to proceed for 30 s at room temperature. Termination of the DNase cleavage reaction, DNA fragment purification, and gel electrophoresis followed standard protocols (24). Footprinting of other transcription complexes (i.e., preinitiation, energy dependent, and postinitiation) required a second incubation step, as described previously (25).…”
Section: Methodsmentioning
confidence: 99%